2017
DOI: 10.1038/s41598-017-18125-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of killing of growing cells and dormant and germinated spores of Bacillus species by black silicon nanopillars

Abstract: Black silicon (bSi) wafers with a high density of high-aspect ratio nanopillars have recently been suggested to have mechanical bactericidal activity. However, it remains unclear whether bSi with the nanopillars can kill only growing bacterial cells or also dormant spores that are harder to kill. We have reexamined the cidal activity of bSi on growing cells, dormant and germinated spores of B. subtilis, and dormant spores of several other Bacillus species by incubation on bSi wafers with and without nanopillar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 43 publications
(78 reference statements)
1
14
0
Order By: Relevance
“…5b), stained red with the BacLight dye mixture, while live dormant spores do not stain well with either of the two dyes in this mixture ( Fig. 5a) (Setlow et al 2016;Ghosh et al 2017;Li et al 2017). As expected, there were significant numbers of red CTABtreated spores ( Fig.…”
Section: Baclight Staining Of Spores Ae Ctab Treatmentsupporting
confidence: 58%
See 2 more Smart Citations
“…5b), stained red with the BacLight dye mixture, while live dormant spores do not stain well with either of the two dyes in this mixture ( Fig. 5a) (Setlow et al 2016;Ghosh et al 2017;Li et al 2017). As expected, there were significant numbers of red CTABtreated spores ( Fig.…”
Section: Baclight Staining Of Spores Ae Ctab Treatmentsupporting
confidence: 58%
“…Spores of different Bacillus strains and species incubated with CTAB or dodecylamine at various temperatures were washed with Tween-20. These spores, as well as untreated sporesAEsteam autoclave treatment for 20 min, were stained without fixation with the BacLight viability stain (ThermoFisher Scientific), and photographed by differential interference contrast (DIC) microscopy and fluorescence microscopy (Ghosh et al 2017). Phase contrast microscopy of untreated, germinated and CTAB-treated spores was carried out under 1009 magnification.…”
Section: Viability On Plates and Microscopy Of Ctab-treated Sporesmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding the disagreements, most researchers agree that mechanical deformation in general and the rupture of cellular components such as cell wall due to large deformations and the penetration of high aspect ratio nano-features play a key role in this regard (Fig. 3) [36,43,[53][54][55][56]. The optimum shape and dimensions of nanopatterns for maximizing the bactericidal behavior are, nevertheless, unknown (Fig.…”
Section: Bactericidal Mechanisms Of Nanopatternsmentioning
confidence: 99%
“…Subsequently, the feature size modulates the interaction of nanopatterns with cells. Not only could surface nanotopography determine stem cell fate, many studies have shown that high aspect ratio nanopatterns are capable of killing bacteria [35,36] and preventing biofilm formation [37].…”
Section: Introductionmentioning
confidence: 99%